2023
DOI: 10.1371/journal.pbio.3002410
|View full text |Cite
|
Sign up to set email alerts
|

Sensory processing in humans and mice fluctuates between external and internal modes

Veith Weilnhammer,
Heiner Stuke,
Kai Standvoss
et al.

Abstract: Perception is known to cycle through periods of enhanced and reduced sensitivity to external information. Here, we asked whether such slow fluctuations arise as a noise-related epiphenomenon of limited processing capacity or, alternatively, represent a structured mechanism of perceptual inference. Using 2 large-scale datasets, we found that humans and mice alternate between externally and internally oriented modes of sensory analysis. During external mode, perception aligns more closely with the external senso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 78 publications
1
4
0
Order By: Relevance
“…Consistent with recent findings in humans and mice 16,17 , Bayesian model comparison indicated a clear superiority of the two-state GLM-HMM over the standard one-state GLM in the S-ketamine experiment (δ BIC = −3.65 × 10 3 ). According to the two-state GLM-HMM, perception fluctuated between an internal mode, shaped by the stabilizing internal prediction y t−1 , and an external mode, dominated by the SAR-weighted input s t .…”
supporting
confidence: 85%
See 2 more Smart Citations
“…Consistent with recent findings in humans and mice 16,17 , Bayesian model comparison indicated a clear superiority of the two-state GLM-HMM over the standard one-state GLM in the S-ketamine experiment (δ BIC = −3.65 × 10 3 ). According to the two-state GLM-HMM, perception fluctuated between an internal mode, shaped by the stabilizing internal prediction y t−1 , and an external mode, dominated by the SAR-weighted input s t .…”
supporting
confidence: 85%
“…We could not attribute between-mode transitions to fatigue, task difficulty (Figure 2D To our knowledge, these results are the first to uncover a neural mechanisms for the slow, task-related fluctuations in perceptual inference that have been observed across variety of tasks in humans and mice [14][15][16][17] . We found that healthy individuals who receive the NMDAR antagonist S-ketamine and patients diagnosed with Scz are prone to an external mode of perception.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…State-dependence of neural activity has been observed in primary sensory cortices (Goris et al, 2014;McGinley, David, et al, 2015;Musall et al, 2019;Nestvogel & McCormick, 2022) and sensory-guided behavior (McGinley, David, et al, 2015). More recently, spontaneous shifts between engaged, biased, and/or disengaged states have been inferred from behavior (Ashwood et al, 2022;Hulsey et al, 2023;Weilnhammer et al, 2023). However, the underlying causes and behavioral functions of these non-stationarities are not unclear.…”
Section: Nonstationarity In Task Performance and Its Causesmentioning
confidence: 99%
“…Early behavioural studies used listreproduction tasks requiring verbal or manual reports of digits or letter series which were either perceptually available, stored in memory, or required integration across both domains (Carlson, Wenger, & Sullivan, 1993;Dark, 1990;Weber, Burt, & Noll, 1986). After a relative hiatus, the question of shifting attention between sensory and internally generated information has attracted renewed interest (Calzolari, Boneva, & Fernández-Espejo, 2022;Gilbert, Frith, & Burgess, 2005;Hautekiet, Verschooren, Langerock, & Vergauwe, 2023;Honey, Newman, & Schapiro, 2017;Poskanzer & Aly, 2023;Servais, Hurter, & Barbeau, 2023;Steel, Silson, Garcia, & Robertson, 2024;Treder et al, 2021;Verschooren, Liefooghe, Brass, & Pourtois, 2019;Verschooren, Pourtois, & Egner, 2020;Verschooren, Schindler, De Raedt, & Pourtois, 2019;Verschooren, Schindler, De Raedt, & Pourtois, 2021;Weilnhammer, Stuke, Standvoss, & Sterzer, 2023). For instance, researchers have replicated earlier work within the visual domain using tasks that require participants to shift between perception and memory on a trial-by-trial basis (Hautekiet et al, 2023;Verschooren et al, 2020;Verschooren, Liefooghe, et al, 2019).…”
Section: Introductionmentioning
confidence: 99%